Symposium 1: What will e-Teaching be like in a future networked university? Symposium Introduction - Guri-Rosenbilt, Sarah; Norberg, Anders; Lapointe, Claire; Power, Michael (Proceedings of the International Conference on Networked Learning, 2018)
As the 21st century unfolds, researchers in higher education, and especially in networked learning, are attempting to peer into the future to better understand the integration of educational technology in light of current trends and future needs. Although a fair amount of research has shed light on learner needs in networked learning (Hodgson & McConnell, 2016; Jandric & Boras, 2015; Hodgson, de Laat, McConnell, & Ryberg , 2014; Jones, 2015), not so much is known about faculty/professors needs and workload (Bentley & Kyvik, 2013; Jonker & Hicks, 2014). Indeed, reports that do come in often deal more with faculty resistance to online and blended learning (Chapman, 2011) than an exploration of the realities faculty face at a time of increasing needs, increasing enrolments, and, overall, an increasing workload in their research-, teaching- and service- related components. Networking is and has been a given in research pursuits among academics for a very long time. The roving scholar in medieval times is an early example of a slowing expanding network of erudition which, gradually, has come to embrace the entire planet, forming, in fact if not in form, a world university system. Yet teaching networks are rarer, especially e-teaching networks (Donnelly & McSweeney, 2010), despite initiatives such as MOOCs which held the promise of sharing knowledge on large networked learning deployments. So, little is actually known about how faculty are harnessing technology to improve their teaching and make it more manageable as a contending priority to research, about how they integrate technology into this part of their workload and what kind of difficulties they face in trying to do so (Power & Morven-Gould, 2011). More to the point, we wonder if e-teaching-based networks and communities of practice are emerging among academics. In an exploration of these issues, this symposium will provide an overview of how faculty networking can apply to e-teaching, and what problematics are embedded in e-teaching. Furthermore, it will look closely at ICT deployment, and online and blended learning as they affect e-teaching. Finally, it will provide a case study based on a networked program approach, documenting the context and its attendant specificities, the actual program replanning required in light of emerging needs, and the new e-teaching practices implemented by faculty. Of special interest to our group is the e-teaching role of the academic as a catalyst in the networking process. Examining how educational leaders use digital networks, Jones, Ferraday & Hodgson stated (2007): "The posts occupied by such workers are often isolated and the use of digital networks has been suggested as a way of developing forms of cooperation and community". Indeed, in higher education, many faculty experience one form or another of isolation and, were it not for their use of networking technologies, they would be virtually disconnected from their respective, far-flung scientific peers. Yet this potential for isolation present, to a degree, in the research realm, is dwarfed by that which faculty experience when it comes to their teaching. To quote Katz (2008): "In scientific research, however, and increasingly in social science and humanities research, IT’s role has been transformational", whereas, "With respect to higher education’s administrative and teaching activities, IT has perhaps not fulfilled its promise to the extent witnessed in some other sectors of the economy. Here, the handicraft traditions of teaching and learning in the academy have, as Trow suggests, “conditioned and constrained IT use”. Indeed, at some colleges and universities, good instructional technology is viewed as a barrier—or even antithetical—to good instruction. Change is slow" (p. xi). We would venture that it is not only slow, it usually occurs within a vacuum of interest, as research, the primary task for which faculty are generally hired, continues to dominate academic life. E-Teaching in Online Learning has usually meant switching from oral exposition to the written word, and merging traditional teaching techniques and modern technological ways of communication. Yet there are indications, insufficiently documented, that faculty are slowly adapting to the rush online by reasserting their role of knowledge developer rather than simple information purveyor through a more judicious and knowledgeable technology selection. Are we seeing the second generation of online learning appearing on the horizon? Perhaps. The goal of this symposium is thus to explore faculty e-teaching problematics and practices in utilizing the wide range of advanced technological capabilities from both the theoretical to the applied perspectives, and at various levels, from macroscopic to microscopic considerations in order to better understand where we are and where we are headed.